Neuronal and Endothelial Transglutaminase-2 Expression during Experimental Autoimmune Encephalomyelitis and Multiple Sclerosis. (1st May 2021) - Pearse, Damien D.; Otero, Peter Anthony; Diaz, Ashley; Pan, Xiaoqi; Ghosh, Mousumi
Graphical abstract: Highlights: In models of EAE and MS, the vasculature and neurons show TG2 induction. Extracellular TG2 colocalizes with FN in disrupted vessels and sclerotic plaques. TG2 is associated with mediators of endothelial inflammation in sclerotic lesions. TG2 expressing neurons show the presence of apoptotic signaling intermediaries. Abstract: Transglutiminase-2 (TG2) is a multifunctional enzyme that has been implicated in the pathogenesis of experimental autoimmune encephalomyelitis (EAE) and multiple sclerosis (MS) using global knockout mice and TG2 selective inhibitors. Previous studies have identified the expression of TG2 in subsets of macrophages–microglia and astrocytes after EAE. The aims of the current investigation were to examine neuronal expression of TG2 in rodent models of chronic-relapsing and non-relapsing EAE and through co-staining with intracellular and cell death markers, provide insight into the putative role of TG2 in neuronal pathology during disease progression. Here we report that under normal physiological conditions there is a low basal expression of TG2 in the nucleus of neurons, however following EAE or MS, robust induction of cytoplasmic TG2 occurs in most neurons surrounding perivascular lesion sites. Importantly, TG2-positive neurons also labeled for phosphorylated Extracellular signal-regulated kinase 1/2 (ERK1/2) and the apoptotic marker cleaved caspase-3. In white and gray matter lesions, high levels of TG2 were also found within the vasculature and endothelial cells as well as in tissue migrating pericytes or fibroblasts, though rarely did TG2 colocalize with cells identified with glial cell markers (astrocytes, oligodendrocytes and microglia). TG2 induction occurred concurrently with the upregulation of the blood vessel permeability factor and angiogenic molecule Vascular Endothelial Growth Factor (VEGF). Extracellular TG2 was found to juxtapose with fibronectin, within and surrounding blood vessels. Though molecular and pharmacological studies have implicated TG2 in the induction and severity of EAE, the cell autonomous functions of this multifunctional enzyme during disease progression remains to be elucidated.